1991
DOI: 10.1016/0095-0696(91)90030-m
|View full text |Cite
|
Sign up to set email alerts
|

Enforcement of pollution regulations in a declining industry

Abstract: A regulatory agency enforcing compliance in a declining industry might recognize that certain plants would close rather than comply, and that these closings would impose large costs on the local community. EPA enforcement activity in the U.S. steel industry is examined for evidence of this result. A three-equation system linking EPA enforcement decisions, company plant-closing decisions, and company compliance decisions is estimated. The results indicate that the EPA directed fewer enforcement actions toward p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(74 citation statements)
references
References 16 publications
7
65
2
Order By: Relevance
“…However, our data raises the possibility that the actual requirements for projects can be lower than the regulatory standards criticized by Shoup (2005). This is similar to the common finding in the environmental regulatory literature that local regulators adjust regulations for the costs and benefits of pollution control at a particular facility (Gray and Deily (1991)). Our indirect method avoids the pitfall of assuming that MPRs apply uniformly and tests whether parking requirements, as they are actually applied, result in economic distortions.…”
Section: Minimum Parking Requirementssupporting
confidence: 64%
“…However, our data raises the possibility that the actual requirements for projects can be lower than the regulatory standards criticized by Shoup (2005). This is similar to the common finding in the environmental regulatory literature that local regulators adjust regulations for the costs and benefits of pollution control at a particular facility (Gray and Deily (1991)). Our indirect method avoids the pitfall of assuming that MPRs apply uniformly and tests whether parking requirements, as they are actually applied, result in economic distortions.…”
Section: Minimum Parking Requirementssupporting
confidence: 64%
“…An analysis of steel plant closing decisions (Deily and Gray (1991) found that steel mills facing more air pollution enforcement were more likely to be closed. A state-level analysis of new plant openings (Gray (1997) There are a set of available technologies (j) among which the firm will choose.…”
mentioning
confidence: 99%
“…Deily & Gray (1991) analyze data from 1977-1986 on EPA enforcement activity, finding that steel mills facing the likelihood of stringent regulatory enforcement (i.e., those with higher predicted probabilities of future 13 inspections) were more likely to close. However, the authors also find that inspectors are more likely to bypass mills with a higher likelihood of closing if inspected.…”
Section: Production Costsmentioning
confidence: 99%